Mandibular canine index: A reliable predictor for gender identification using study cast in Indian population - Siddharth Kumar Singh; Anjali Gupta; B Padmavathi; Sandeep Kumar; Sayak Roy; Arunoday Kumar (Wolters Kluwer Medknow Publications, 2015)
Context: Various methods are used for gender identification in anthropologic and forensic investigations. The canine tooth is widely used for gender determination because of its sexual dimorphism and durability in the oral cavity. Mandibular canine index (MCI) is one of the most reliable and valid predictor for gender identification. Aim: To assess the reliability of MCI in gender determination in Indian population. Settings and Design: This was an experimental study involving the preparation of plaster models of 100 individuals residing in Udaipur, Rajasthan, India. Of these 45 were males and 55 were females. Both sexes were in the age group of 20-30 years. Study casts were prepared for all individuals and the measurements of mandibular canine teeth were taken. The MCI was calculated using standardized equation. In addition, the percentage of sexual dimorphism was calculated. Statistical Analysis Used: Independent sample t-test was used. P < 0.05 was considered statistically significant. Results: There was a significant difference (P < 0.05) observed between inter-canine distance, right and left canine width and right and left MCI between males and females. Sexual dimorphism is more on left permanent mandibular canine teeth than right permanent mandibular canine teeth. The overall percentage of accuracy observed was 85.5%. Conclusions: Study findings reveal that MCI can be used a reliable predictor for gender determination in Indian population and can form the basis of anthropologic and forensic investigations.